2015
DOI: 10.1530/rep-14-0614
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra and etanercept prevent embryo loss in pregnant nonobese diabetic mice

Abstract: Bacteria and viruses activate the host innate immune response via Toll-like receptor (TLR)-involved signaling and potentially cause pregnancy failure. TLR7 and TLR9 respond to single-stranded RNA (a viral intermediate) and hypomethylated CpG DNA motifs (specific molecular constituents of bacteria) respectively. In this study, we treated murine RAW264.7 cells with R837, CpG1826, or a combination of the two. RT-PCR was performed to detect cytokines, Tlr7, and Tlr9. WT and nonobese diabetic murine embryo resorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The miscarriage rate was 30% for pregnancies not on anakinra vs 10% for pregnancies on anakinra in the aforementioned cryopyrin-associated periodic syndromes study [3]. An additional study looking at murine models with an elevated IL-1 environment found that when these mice were given IL-1 inhibition, it prevented pregnancy loss [10]. A common theme among prior case exposures is flaring disease activity when taken off anakinra, but good response after the medication is restarted.…”
Section: Discussionmentioning
confidence: 99%
“…The miscarriage rate was 30% for pregnancies not on anakinra vs 10% for pregnancies on anakinra in the aforementioned cryopyrin-associated periodic syndromes study [3]. An additional study looking at murine models with an elevated IL-1 environment found that when these mice were given IL-1 inhibition, it prevented pregnancy loss [10]. A common theme among prior case exposures is flaring disease activity when taken off anakinra, but good response after the medication is restarted.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that TLR9 is capable of suppressing angiogenesis (127) and that aberrantly activated ligand binding to different TLRs may significantly influence pregnancy outcomes. In a relatively recent study, it was demonstrated that inhibition of TLR activation and thus inhibition of downstream signaling, could not prevent embryo resorption in the absence of dNK cells (105,128). Differential expressions of TLRs throughout pregnancy and in preeclampsia, suggest that these receptors might represent potential therapeutic targets.…”
Section: Toll-like Receptors In Preeclampsiamentioning
confidence: 99%
“…A more general correlation between IL1RN*2 allele and presence of autoinflammatory disease strongly supports a role in the control of the inflammatory response, and iRSA may be included within this group of diseases 15,35 . New evidence from murine models has shown prevention of miscarriage by blocking IL-1β 36 .…”
Section: Discussionmentioning
confidence: 99%